Computer-Aided Diagnosis of Speech Disorder Signal in Parkinson’s Disease (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Computer-aided diagnosis (CAD) can be used as a decision support system by physicians in the diagnosis and treatmentof disordered speech especially those who specialize in neurophysiology diseases. Parkinson's disease (PD) is aprogressive disorder of the nervous system that affects movement. It develops gradually, sometimes starting with a barelynoticeable tremor in speech. It has been found that 80% of persons with PD reported speech and voice disorders.Parkinson's disease symptoms worsen as the condition progresses over time. Therefore, Speech may become soft orslurred and these deficits in speech intelligibility impact on health status and quality of life. Different researchers arecurrently working in the analysis of speech signal of people with PD, including the study of different dimensions in speechsuch as phonation, articulation, prosody, and intelligibility. Here, we present the characteristics and features of normalspeech and speech disorders in people with PD and the types of classification for implementation of the efficacy oftreatment interventions. The results show that our classification algorithm using ANN is outperformed KNN and SVM. ANNis a practical and useful as a predictive tool for PD screening with a high degree of accuracy, approximately 96.1% of acorrect detection rate (sensitivity 94.7%, and specificity 96.6%). Based on the high levels of accuracy obtained by ourproposed algorithm, it can be used for enhancing the detection purpose to discriminate PD patients from healthy people.Our algorithm may be used by the clinicians as a tool to confirm their diagnosis.